Tradisi Begalan di Banyumas: Simbolisme, Ritual, dan Nilai Budaya dalam Upacara Pernikahan Adat Jawa - Santi, Devita Rachma (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
The Begalan tradition is a unique and important tradition in the series of traditional Javanese wedding processions, especially in the Banyumas area. This tradition not only serves as entertainment for invited guests, but also contains a very deep symbolic meaning, related to the life journey and responsibilities that the newlywed couple will face. In the Begalan ceremony, several household utensils carried by the figures in the procession have their own philosophical value which symbolizes the roles and responsibilities of husband and wife in domestic life. This research is a qualitative descriptive research. This data collection technique is through observation, interviews and literature review. The object of this research is related to symbolic, ritual and cultural values in the Begalan tradition in Banyumas.